Influence of Bi–Fe additive on properties of vanadium phosphate catalysts for n-butane oxidation to maleic anhydride - Goh, Chee Keong; Yap, Taufiq Yun Hin; Hutchings, Graham John; Dummer, Nicholas F.; Bartley, Jonathan K. (Elsevier, 2008)
The physico-chemical and catalytic properties of three ways of modified catalysts were studied, i.e. (i) the addition of both Bi and Fe (nitrate form) during the refluxing VOPO4·2H2O with isobutanol (Catalyst A), (ii) the simultaneous addition of BiFe oxide powder in the course of the synthesis of precursor VOHPO4·0.5H2O (Catalyst B) and (iii) the mechanochemical treatment of precursor VOHPO4·0.5H2O and BiFe oxide in ethanol (Catalyst C). It was found that surface area of the modified catalysts has increased except Catalyst B. The reactivity of the oxygen species linked to V5+ and V4+ was studied by using H2-TPR, which also affected the catalytic performance of the catalyst. The conversion of n-butane decreases with an increment of oxygen species associated with V5+.